MODERN PROBLEMS OF BIOLOGICAL SAFETY (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2022)
The given article describes biosafety problems, which exist in our days, and alsothe readiness of the country to react and eliminate the consequences of biological hazards includingprotection of the population and a system of their life support and agriculture as well
Keywords: biosafety, biological agents, infectious diseases, hazard of import, diagnostic system, Convention on Biological Weapon & Toxines (CBWT)